Photosynthesis Rate, Sugar and Starch Content of Sago Leaves (Metroxylon sp.) at Different Preparation Methods of Sago Seedlings - Ayulia, Liska; Djoefrie, M.H.B.; Agusta, Herdhata (Department of Agronomy and Horticulture, IPB University, 2022)
Photosynthesis rate plays a significant role in plant growth and development. A study was conducted to determine the best methods to grow sago planting materials from sago suckers. Photosynthesis rate, stomatal density, intercellular CO2 concentration, stomatal conductance, transpiration, sugar and starch content of the sago leaves from different methods of planting was determined. The field experiment was carried out at the Cikabayan Experimental Station from January 2020 to February 2021; the leaf morphology was conducted at the Microtechnical Laboratory and Testing Laboratory of the Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia. The treatments for the sago seedlings were immersion of the bare-rooted seedlings in water, immersion in water with media mix in polybags, transplanted to media mix in polybags, and immersion of bare-rooted seedlings for 4 weeks in water followed by transplanting to media mix in polybags. The study was arranged using a single factor a completely randomized block design, and quantitative data was analyzed using Microsoft Excel 2013 and the SAS. Stomatal density and photosynthetic rate were not significantly different between treatments. In contrast, the sugar content of immersed seedling without polybags for one month followed by transplanting to polybag had the best growth compared to those from other treatments, both at the nursery phase and post-transplanting phase. All planting methods resulted in good quality planting materials. At the nursery phase, sago seedlings immersed in water method grew the best; at the post-transplanting phases seedlings immersed bare-rooted for one month followed by transplanting to polybags grew better than those with other treatments